IMPLEMENTASI KONSELING INDIVIDU TEKNIK COGNITIVE DEFUSION UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP - Anjali Audrey Puspasari; Ade Irma Noviyanti; Dewi Masyitoh (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
Self-confidence is an important aspect in students' psychological development. Several eighth-grade students were found to have low self-confidence, demonstrated through behaviors such as fear of public speaking, hesitation in making decisions, and lack of activity in class activities. This problem needs to be addressed immediately through an appropriate counseling approach. This study aims to implement and evaluate the cognitive defusion technique in individual counseling to improve students' self-confidence. The approach used was a single-subject experimental research (Single-Case Experimental Design) with an A-B format. In phase A (baseline), an initial self-confidence measurement was conducted without treatment. Furthermore, in phase B (intervention), individual counseling using the cognitive defusion technique was conducted for several sessions. The subjects in this study were eighth-grade students who had been identified as having low self-confidence. The instrument used was a validated self-confidence questionnaire. Data analysis used quantitative descriptive analysis. Based on the results and discussion of the study, it can be concluded that individual counseling using the cognitive defusion technique is effective in improving the self-confidence of students with low self-confidence. This was demonstrated by an increase in AD students' self-confidence questionnaire scores from a baseline of 50 (low category) to a final score of 90 (high category) after four sessions of intervention. This gradual improvement indicates that the technique successfully helped students break free from negative thoughts that hindered their self-confidence.